Dietary selenium nanoparticles alleviate heat stress-induced reproductive impairment in Onychostoma macrolepis, with MeSeCys as a key bioactive selenium species - Chao Zhu; Weiping Pan; Jianbo Zheng; Shili Liu; Meili Chi; Wenping Jiang; Shun Cheng; Junzhi Luo; Wuzi Dong; Zhilong Chen; Fei Li (Theriogenology, 2026)

Gut microbiota and metabolic profiles alteration during in vitro fecal fermentation of an immunostimulatory polysaccharide from Astragalus membranaceus - Lu Xu; Kailin Li; Tim-Fat Shum; Qianru Lin; Kelvin Sze-Yim Cai; Franco King-Chi Leung; Cheng Li; Jiachi Chiou (Food Research International, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Functional characterization of the Cbr1 gene in regulating alkaline tolerance in grass carp - Jianbo Zheng; Yi Xu; Qi Chen; Fei Li; Shili Liu; Chao Zhu; Shun Cheng; Wenping Jiang; Meili Chi; Junzhi Luo; Caiyan Li; Xiaohui Xu; et al. (Aquaculture, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Generative diffusion model for environmental diffusion problems - Yuxun He; Bo Jiang; Yun Cheng; Xiangyu Chi; Meicheng Liao; Chenliang Tao; Peng Li; Hao Qiu; Zhen Cheng (Environmental Modelling & Software, 2026)

Multiscale optimization of solar interfacial evaporation systems: toward a new design paradigm for next-generation, high-efficiency solar-driven energy harvesting - Cheng Chi; Shiyu Liu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Huchuan Yan; Cui Lai (Desalination, 2026)

Assessing the Potential of a Formalin‐Killed Cells (FKC) Vaccine Against Edwardsiella anguillarum in Milkfish ( Chanos chanos ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum causes Edwardsiellosis in fish, resulting in severe internal organ lesions and substantial economic losses in aquaculture. The limited efficacy of antibiotics in treating this disease, coupled with concerns regarding resistance and side effects, has driven interest in exploring fish vaccines. Various vaccine candidates derived from E. anguillarum, including inactivated cells and protein subunits, have shown potential. Here, we developed a vaccine against E. anguillarum in milkfish, and its efficacy was evaluated through vaccination challenge trials using milkfish as the target species. The formalin‐killed vaccine (FKC) in combination with an adjuvant exhibited superior efficacy, achieving a relative percent survival (RPS) of 83.4%. Furthermore, the agglutination titers indicated a robust immune response in the FKC + Adjuvant group, suggesting a potent and sustained antibody response. Additionally, serum lysozyme activity was significantly higher in vaccinated fish than in controls. Immune‐related gene expression analysis in spleen and head kidney revealed that IL‐1β peaked at 14 days post‐vaccination, indicating early pro‐inflammatory response, while MHC‐II showed progressive elevation, suggesting sustained antigen presentation and humoral immunity. Overall, this study underscores the effectiveness of the FKC + Adjuvant combination in enhancing immune response and protecting against bacterial pathogens in aquaculture, presenting a promising strategy for disease control.

Influence of Multi-field Coupling Effect on Coal Porosity in the Process of Liquid Nitrogen Fracturing in Watery Coal - Cheng Wang; Li Liu; Yongfei Jin; Yiru Fan; Haifei Lin; Min Yan; Chi-Min Shu (Natural Resources Research, 2026)

Influence of suspended particulate matter input on phytoplankton community structure in estuarine environments - Xinjie Wang; Yimei Xi; Kuo Fang; Cheng Li; Yongbin Li; Shaofeng Wang; Ran Bi; Zhanyou Chi; Jiashen Tian; Xiangfeng Zeng (Marine Environmental Research, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Genomic insights and vaccine evaluation of a virulent MLST ST234 Bacillus cereus infecting Asian sea bass (Lates calcarifer) - Li-Wu Cheng; Qiong-Yi Huang; Nopadon Pirarat; Abisheik Rajandran; Sayuj Poudyal; Pei-Chi Wang; Shih-Chu Chen (Fish & Shellfish Immunology, 2026)

Multifunctional LiSCN modified SnO2 electron transport layer for efficient and stable n-i-p perovskite solar cells - Liang Lei; Song Zhang; Ting Zhu; Cheng Gao; Yafei Liu; Zhangbo Lu; Zhitao Shen; Ming Li; Dan Chi; Jianlong Kou; Shunchang Liu; Shihua Huang (Chemical Engineering Journal, 2026)

Molnupiravir: A Prodrug of the Ribonucleoside β‐D‐N4‐Hydroxycytidine Triphosphate Inhibits the Propagation of Nervous Necrosis Virus in Grouper Brain Cells - Chen‐Kung Chi; Vertika Bajpai; Chen‐Hung Li; Hsin‐Yi Tsai; Chien‐Wen Chen; Chao‐An Cheng; Hsia‐Wei Liu; Chi‐Yao Chang (Journal of Fish Diseases, 2026)
Nervous necrosis virus (NNV) is the causative agent of viral nervous necrosis, otherwise known as viral encephalopathy and retinopathy in larval and juvenile marine fish worldwide. The pandemic outbreaks have caused nearly 100% mortality in hatcheries, leading to significant economic losses in the aquaculture industry. Since NNV attacks the insufficient immune competence fish at early developmental stages, there is an urgent need for effective antiviral drugs. Several nucleoside analogues, including Molnupiravir, have been developed to target viral RNA‐dependent RNA polymerase (RdRp). This study examines the antiviral activity of Molnupiravir against NNV isolated from giant grouper (GG), Epinephelus lanceolatus (Bloch), using grouper brain (GB) cells as an infection model. The inhibition concentration for 50% of maximal effect (EC 50 ) of Molnupiravir on GGNNV propagation in GB cells was determined as 1.87 μM. Surprisingly, the titre of GGNNV reduced 50,000 at 100 μM of Molnupiravir treatment at 4‐day post‐infection, whereas treatment with 200 μM of Molnupiravir resulted in a 10 5 reduction in viral titre. The inhibition of viral replication and translation was further examined using RNA‐fluorescence in situ hybridization (FISH) and immunocytochemistry detection, respectively. Moreover, administration of 100 μM Molnupiravir at early time 0 hpi resulted in a dramatic decrease in viral load, reducing cell‐associated virus by approximately 4000‐fold and released virus by 6000‐fold. Finally, the molecular docking simulation model supports the interaction between NHC‐TP and GGNNV RdRp for the successful therapeutics. These results demonstrated that Molnupiravir is a very effective therapeutic drug for controlling viral nervous necrosis caused by NNV infection.

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Improving resilience monitoring in non-stationary systems via a robust data-chunking algorithm - Linhai Cheng; Qiang Tang; Nan Lu; Chi Xu; Babak M.S. Arani; Changjia Li; Yafeng Wang; Xiangyi Li; Phuping Sucharitakul; Shuai Wang; Jie Wei; Junran Li; et al. (Science Bulletin, 2026)

Quantifying multi-objective trade-offs in maize production and greenhouse gas emissions under brackish water irrigation using GAM–NSGA-II - Chenchen Wei; Yu Wang; Yanbing Chi; Peiling Yang; Cheng Yan; Yalong Li; Miaomiao Shi; Baokun Xu; Yang Xu; Miaoying An (Field Crops Research, 2026)

Towards negative-carbon biohydrogen: A dual-function wollastonite strategy for enhanced fermentation and CO2 sequestration - Weiming Li; Can Jin; Huida Duan; Fangcao Li; Zhangxun Huang; Haodong Zhao; Xiaoman Yu; Yimei Xi; Xiangfeng Zeng; Yongfeng Jia; Chi Cheng (Chemical Engineering Journal, 2026)

Grass carp ( Ctenopharyngodon idella ) resist heat stress by maintaining mitochondrial quality and enhancing energy production - Xiaotian Zhang; Xianfang Yan; Pengju Li; Chi Wang; Cheng Zhang; Hong Ji; Haibo Yu (Journal of Fish Biology, 2026)
This study aims to explore the resistance mechanism of grass carp ( Ctenopharyngodon idella ) to heat stress (HS). Grass carp were cultured at 28°C, and then exposed to 30°C, 32°C or 34°C with a heating rate of 1°C/d, respectively. The results show that serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) levels and liver malondialdehyde (MDA) content significantly increased after HS. In contrast, liver total antioxidant capacity (T‐AOC) was significantly reduced after HS. Additionally, serum triglyceride (TG) and free fatty acid (FFA) levels increased after HS. Notably, the hepatic adenosine triphosphate (ATP) content of grass carp exposed to 30°C and 32°C was significantly higher than that of those exposed to 28°C. However, the liver ATP content of grass carp exposed to 34°C was significantly reduced compared to other groups. Further, the liver mitochondrial DNA copies significantly increased after HS. The expression of mitochondrial biogenesis genes ( pgc‐1α , nrf1/2 , tfam ) and mitophagy genes ( beclin1 , atg5 , atg7 , pink1 , parkin ) was upregulated in grass carp after HS. However, the expression of mitochondrial fission gene ( drp1 ) was significantly upregulated in grass carp exposed to 34°C compared to other groups, whereas no corresponding change was observed in the expression of mitochondrial fusion gene ( mfn1/2 ) in grass carp exposed to 34°C. In conclusion, when grass carp were exposed to 30°C or 32°C, mitochondrial homoeostasis can be maintained via regulating mitochondrial quality, providing enough energy for grass carp to resist HS. However, when grass carp was exposed to 34°C, mitochondrial homoeostasis was impaired, leading to inadequate energy for grass carp to resist HS.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Development of a sex-linked PCR marker for non-invasive and early sex determination in largemouth bass (Micropterus salmoides) - Fei Li; Jianbo Zheng; Shili Liu; Shun Cheng; Wenping Jiang; Meili Chi; Chao Zhu; Miao Peng; Qinghui Meng (Conservation Genetics Resources, 2026)

Integrated analysis of PM2.5 chemical characteristics and multi-pollutant health risks in Central Taiwan: Implications for optimizing the air quality health index (AQHI) during the COVID-19 pandemic - Po Jui Chen; Tuan Hung Ngo; Shahzada Amani Room; Yuan Cheng Hsu; Yan Cing Li; Shih Yu Pan; Ta Chih Hsiao; Yu-Cheng Chen; Kai Hsien Chi (Science of The Total Environment, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

From behavior to taste: Developmental trajectories of anxiety-like phenotypes unveil a neuroendocrine link to flesh quality in economic crustaceans - Hengtong Liu; Sisi Sheng; Yiming Li; Wanting Huang; Wenbin Liu; Haochen Wang; Cheng Chi; Dingdong Zhang (Food Bioscience, 2026)

Molten salt upcycling of waste PET into high-performance lithium-ion battery anodes - Hao Zhang; Junjie Jiang; Mengge Xing; Liangyuan Cheng; Qi Zhang; Shidong Li; Yihan Qian; Xiong Qian; Chi Sun Poon; Jiashen Meng (Chemical Engineering Journal, 2026)

Balancing Accuracy and Speed: Improved D-FINE for Real-Time Ocean Internal Wave Detection - Lu Yu; Yanping Tian; Jie Chen; Cheng Chi; Tingting Li; Jianwei Li (Journal of Marine Science and Engineering, 2026)
Ocean internal waves (IWs), induced by density stratification and fluid perturbations, are significant oceanic phenomena prevalent across global oceans, profoundly impacting marine environments and engineering safety. Although one-stage object detection models are favored in practical applications due to their efficient inference, they often suffer from insufficient accuracy in IW detection tasks. To address this, we introduce a novel one-stage, anchor-free detection approach based on Transformer for IW detection, proposing a new algorithm named IW-D-FINE, which balances detection accuracy and inference efficiency. On the public SAR dataset, IW-D-FINE achieves an AP@0.5 of 90.5, significantly outperforming existing one-stage methods while maintaining faster inference speeds than mainstream two-stage models. Furthermore, to mitigate the scarcity of internal wave samples, we construct a small-scale IWs dataset, YH3-IW-2025, and validate the algorithm thoroughly on this dataset. Experimental results demonstrate that IW-D-FINE exhibits robust performance under complex background interference, highlighting its application potential and scalability in IW detection tasks.

Suppression of ethylene metabolism serves as a key factor underlying high temperature-induced promotion of anthocyanin synthesis of peach skin - Yingtong Zhang; Lijuan Sun; Ming Chi; Xiaoyue Cheng; Huali Hu; Hongsheng Zhou; Miaomiao Yao; Zhengbing Guo; Jun Ling; Pengxia Li (Postharvest Biology and Technology, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Whole‐Genome Single Nucleotide Polymorphism Analysis and High‐Resolution Melting ( HRM ) Differentiation of Edwardsiella anguillarum and Edwardsiella piscicida - Atiek Rahmawaty; Li Wu Cheng; Jue‐Liang Hsu; Shun Maekawa; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2026)
This study aimed to develop a method to differentiate between two closely related bacterial species within the genus Edwardsiella , namely Edwardsiella anguillarum and Edwardsiella piscicida , which cause Edwardsiellosis in fish aquaculture. Whole‐genome single nucleotide polymorphism (SNP) analysis was conducted to assess the genetic relationships among E. piscicida , E. anguillarum and Edwardsiella ictaluri . SNP distance matrices and phylogenetic trees demonstrated that isolates within each species clustered together, confirming genetic SNP distinctiveness. SNP annotation and distance comparisons identified key genes— artI , dnaK , hlyB , ubiB , hutW , ydgD , MCP and fliC —that exhibited significant divergence. We designed specific primers targeting SNPs in these genes and used these primers for real‐time PCR and High‐Resolution Melting (HRM) analysis. HRM analysis using designed primer pairs revealed distinct melting temperature ( Tm ) peaks for E. anguillarum and E. piscicida . HRM analysis of 37 isolates that were previously identified as E. tarda based on phenotypic characteristics identified them as either E. anguillarum (35) or E. piscicida (2). These results showed that hlyB was the most reliable target gene for distinguishing between E. anguillarum and E. piscicida . The HRM technique is a fast, cost‐effective method for differentiating these closely related bacterial species and provides insights into the genetic variation among different species of Edwardsiella and host‐specific strains.

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

The comparison between multiple linear regression and random forest model in predicting environmental noise and its frequency components level in Hong Kong using a land-use regression approach - Chui Hei Wong; Zhiyuan Li; Steve Hung Lam Yim; Ta-Yuan Chang; Chung Ling Man; Chin Ho Cheng; Timothy Chi-yui Kwok; Kin Fai Ho (Environmental Research, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Highly thermally stable anti-opalite TiOx/ZnO-carbon for achieving targeted transfer of NH3 oxidation products in multiphase catalysis - Li Sun; Peng Zhou; Xiaolin Tang; Yuming Zhou; Bo Yuan; Zhican Lu; Chongtao Ding; Weihang Cheng; Yixin Liu; Xingang Wang; Chi Huang (Chemical Engineering Journal, 2025)

Conserved domains of flagellin as adjuvants for an inactivated vaccine against porcine epidemic diarrhea virus - Haroon Afzal; Nguyen-Thanh Hoa; Asad Murtaza; Thu-Dung Doan; Yao-Chi Chung; Guan-Ming Ke; Li-Ting Cheng (The Veterinary Journal, 2025)

Impact of pretreatment methods on hydrogen and ethanol co-production from brown algae: Energy recovery and cost analysis - Zhongliang Shi; Chi Cheng; Mengyang Bian; Weiming Li; Yimei Xi; Shuhua Yao; Xiangfeng Zeng; Yongfeng Jia (Journal of Environmental Chemical Engineering, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Self-assembled triboelectric nanogenerators with optimized surfaces for high-g accelerometers in extreme environments - Chi Zhang; Yizhou He; Qi Wang; Weifan Pan; Zhiqiang Xiang; Shaorong Li; Xiaowei Guo; Cheng Yang (Chemical Engineering Journal, 2025)

High humidity-resisted all-wood-based triboelectric nanogenerator for energy harvesting and human motion monitoring - Peiyao He; Xiaojun Li; Min Wang; Dong Lv; Jingqiu Wang; Linjun Zou; Ruixiang Cheng; Ran Yin; Xiang Chi; Jian Li; Likun Gao (Chemical Engineering Journal, 2025)

Changes in the physiological indicators and gene expression for grass carp (Ctenopharyngodon idella) in response to alkaline stress - Qi Chen; Jianbo Zheng; Yi Xu; Fei Li; Shili Liu; Wenping Jiang; Meili Chi; Shun Cheng; Haiqi Zhang (Aquaculture International, 2025)

Effects of calcium levels in water on growth, calcium deposition, molting, and immunity of Chinese mitten crab (Eriocheir sinensis) - Ronghua Zhou; Qiyong Qiu; Yingying Zhou; Shiyu Qin; Xiaoyan Jia; Wei Qiang; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2025)

Mapping drag coefficient using CFD and machine learning with application to urban canopy model - Jie Chen; Ziwei Mo; Congyu Li; Wai-Chi Cheng; Chun-Ho Liu (Sustainable Cities and Society, 2025)

RNA target-independent non-canonical activation (RINCA) of Cas13 trans-nuclease activity - Wenjun Liu; Xuena Zhu; Yuanyuan Xue; Xiaoyan Wang; Lei Chang; Shanshan Wang; Ling Li; Jinyan Huang; Ying Zhang; Cheng Jiang; Hongjie Chi; Yanbin Zhang; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Multiple defects construction of Co loading on Ni foam to activate water for promoting catalytic ozonation of dichloromethane - Yongtao Li; Chujun Luan; Fawei Lin; Xueyan Zhu; Beibei Yan; Zhanjun Cheng; Guanyi Chen; Chi He (Journal of Hazardous Materials, 2025)

Synergistic ammonium and carbon removal in aquaculture effluent using red seaweed Agardhiella subulata - Zi-Yan Xu; Bonien Chen; Chiu-Hui Kuo; Chen-Hsun Liu; Li-Lian Liu; Yu-Yun Chen; Jui-Kuo Kao; Feng-Cheng Wu; Pao-Chi Liao; Kuohsun Chiu (Environmental Science and Pollution Research, 2025)

Seismic risk and loss assessment models for highway continuous girder bridges in large-scale zones - Si-Qi Li; Peng-Fei Qin; Peng-Chi Chen; Yi-Ru Li; Jia-Cheng Han; Jian Zhong (Soil Dynamics and Earthquake Engineering, 2025)

Impacts of environmentally persistent free radicals on the denitrification toxicity of photoaged tire wear particles in estuarine sediments - Jinyu Ye; Yuhan Zhang; Yuan Gao; Chen Li; Baoping Zou; Ruotong Cheng; Baoyan Chi; Xiangdong Xue; Carlos Domingo-Félez (Journal of Hazardous Materials, 2025)

Seawater intrusion causes substantial release of dissolved organic carbon in coastal paddy soils - Wenting Chi; Yang Yang; Pei Wang; Chao Guo; Zebin Hong; Shiwen Hu; Kuan Cheng; Shan Wang; Han Li; Qi Wang; Ying Li; Yang Wu; et al. (Geochimica et Cosmochimica Acta, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Optimized Deployment of Generalized OCDM in Deep-Sea Shadow-Zone Underwater Acoustic Channels - Haodong Yu; Cheng Chi; Yongxing Fan; Zhanqing Pu; Wei Wang; Li Yin; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2025)
Communication in deep-sea shadow zones remains a significant challenge due to high propagation losses, complex multipath effects, long transmission delays, and strong environmental influences. In recent years, orthogonal chirp division multiplexing (OCDM) has demonstrated promising performance in underwater acoustic communication due to its robustness against multipath interference. However, its high peak-to-average power ratio (PAPR) limits its reliability and efficiency in deep-sea shadow-zone environments. This study applies a recently proposed generalized orthogonal chirp division multiplexing (GOCDM) modulation scheme to deep-sea shadow-zone communication. GOCDM follows the same principles as orthogonal signal division multiplexing (OSDM) while offering the advantage of a reduced PAPR. By segmenting the data signal into multiple vector blocks, GOCDM enables flexible resource allocation, optimizing the PAPR without compromising performance. Theoretical analysis and practical simulations confirm that GOCDM preserves the full frequency diversity benefits of traditional OCDM, while mitigating PARR-related limitations. Additionally, deep-sea experiments were carried out to evaluate the practical performance of GOCDM in shadow-zone environments. The experimental results demonstrate that GOCDM achieves superior performance under low signal-to-noise ratio (SNR) conditions, where the system attains a 0 bit error rate (BER) at 4.2 dB and 6.8 dB, making it a promising solution for enhancing underwater acoustic communication in challenging deep-sea environments.

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Glycerol monolaurate reduces lipid deposition and promotes the health of liver and intestine in grass carp fed with high-fat diet - Chi Wang; Pengju Li; Haibo Yu; Yunhe Li; Cheng Zhang; Xiaotian Zhang; Hao Li; Tian Li; Hong Ji (Animal Feed Science and Technology, 2025)

Nuclear translocation of β-catenin and migration of arecoline-induced oral cancer cells reduced by Taiwanin E via p-GSK3β downregulation - Chi-Cheng Li; Marthandam Asokan Shibu; Wei-Wen Kuo; Yueh-Hsiung Kuo; Yun-Peng Chao; Chun-Hsu Yao; Da-Tian Bau; Pei-Jei Lio; Chung-Jen Chiang; Chih-Yang Huang (Molecular & Cellular Toxicology, 2025)

Ferrosilicon alloy as both reactant and catalyst for hydrogenation of SiCl4: Thermodynamics, mechanism, and kinetics studies - Zheng-Peng Wang; Zi-Yi Chi; Huai-Qiang Dou; Xue-Gang Li; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Harvesting rice straw management synergies for lifecycle environmental and economic sustainability - Suraj Negi; Yu-Chi Cheng; Shan-Li Wang; Shuay-Tsyr Ho; Shu-Yuan Pan (Science of The Total Environment, 2025)

GmHSP40.1, a nuclear-localized soybean J domain protein, participates in regulation of flowering time through interacting with EMF1 and JMJ14 - Chi Zhang; Hu-Jiao Lan; Li-Na Liao; Min-Jun Huang; Wei Xu; Hui Zhang; Qianqian Ma; Feng Li; Ninghui Cheng; Paul A. Nakata; Steven A. Whitham; Jian-Zhong Liu (Plant Science, 2025)

Age constraints on the Ediacaran carbonate carbon isotope excursions in the Tarim Block: Evidence from in situ U–Pb dating of dolostone - Wen-Wu Huang; Liang-Liang Zhang; Di-Cheng Zhu; Li Liu; Xiao-Wei Li; Jin-Cheng Xie; Qing Wang; Hao-Yin Chi (Precambrian Research, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

The biodegradable poly(3-hydroxypropionate) from acrylic acid via 3-hydroxypropionic acid: Studies on catalytic hydration and self-polycondensation - Zhen-Yang Lu; Zhao Chen; Zhuo Li; Zi-Yi Chi; Xue-Gang Li; Shuang-Yu Wei; Cheng-Wei Liu; Wen-De Xiao (Chemical Engineering Journal, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Green preparation of low-molecular-weight galactomannan from Gleditsia sinensis and mechanistic investigation on ameliorating nonalcoholic fatty liver disease - Chi Feng; Xichuang Cheng; Mula Na; Fenglun Zhang; Jiufang Duan; Li Ji; Jianxin Jiang (Food Research International, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

α-Glucosidase inhibitory activities of aromatic compounds from the rhizomes of Alpinia galanga - Yueh-Hung Cheng; Po-Chun Chen; Zakhele M. Dlamini; Jia-Wei Li; Bongani S. Dlamini; Yu-Kuo Chen; Chi-I Chang (Medicinal Chemistry Research, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

The patterns and controlling factors of soil carbon and nitrogen in the water level fluctuation zone of the Three Gorges Reservoir - Chenchen Wei; Yuan Qiu; Yanbing Chi; Yalong Li; Wenhao Yi; Yujie Zhou; Cheng Yan (Journal of Soils and Sediments, 2025)

Enhanced immune response with baculovirus-expressed BoHV-1 glycoprotein D in vaccine development - Nguyen-Thanh Hoa; Haroon Afzal; Uudamsaikhan Gundegmaa; Odbileg Raadan; Li-Ting Cheng; Chun-Yen Chu; Thu-Dung Doan; Yao-Chi Chung (The Veterinary Journal, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Immune response and protection efficacy of formalin‐killed vaccines against Streptococcus iniae in four‐finger threadfin Eleutheronema tetradactylum - Yin‐Ze Shi; Andre Giovanni; Li‐Wu Cheng; Wen‐Rou Huang; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Four‐finger threadfin, Eleutheronema tetradactylum farming in southern Taiwan has been facing disease problems caused by Streptococcus iniae since 2018. The development of a vaccine against infectious S . iniae in the cultured threadfin industry is necessary. Thus, this study aimed to examine the efficacy of threadfin immunized formalin‐killed cells (FKC) from S . iniae GSI‐111 for 42 days post‐vaccination (dpv) using two doses of FKC alone (a booster at 14 dpv) as group A, and FKC mixed with ISA763A adjuvant using a single dose as group B or double doses as group C. Immunoglobulin (Ig)‐M was purified from threadfin, and rabbit anti‐threadfin IgM polyclonal antibodies were used to detect antibody level in immunized fish; the vaccinated group A displayed higher levels at 3 dpv and all vaccinated treatments demonstrated high antibody levels between 14 and 42 dpv. All vaccine groups showed significantly higher values of lysozyme activity at 42 dpv compared with the control group; the vaccinated A group peaked at 14 dpv. The expression profiles of pro‐inflammatory and immune‐related genes, TNF‐α , IL‐12A , and C2 were upregulated at 3 dpv, while CD8A and chemokine receptor CXCR4 were upregulated at 42 dpv. Finally, the threadfins were challenged with S . iniae at 42 dpv. The average relative percent survival was 96% for vaccination A and B treatments, and 100% for vaccination C treatment. In summary, this study demonstrated that FKC vaccines whether formulated with an adjuvant could stimulate immune response and effective protect threadfins against S . iniae infection.

Transport processes of dissolved and particulate nitrogen and phosphorus over urban road surface during rainfall runoff - Yang Xiao; Chi Zhang; Taotao Zhang; Bin Luan; Jiaming Liu; Qiang Zhou; Chentao Li; Haoke Cheng (Science of The Total Environment, 2024)

A nucleus-targeting fluorescence probe for rapid diagnosis of colorectal cancer - Yonggan Xue; Jimei Chi; Bobin Ning; Lijun Cheng; Wenchen Wang; Qingyu Meng; Liang Huang; Mu Ke; Sen Li; Meng Su; Baoqing Jia (Chemical Engineering Journal, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Enzyme induced polymer degradation as a pathway to create microbial habitats for biomanufacturing intensification - Wei Cheng; Huilin Wen; Haixia Shen; Chenwei Fu; Erkuang Miao; Dongbao Li; Xiaoqiang Chen; Chi Hu; Ziyi Yu (Chemical Engineering Journal, 2024)

Comparative pathogenicity and histopathological analysis of Edwardsiella anguillarum intraperitoneal infection in milkfish ( Chanos chanos ), Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ) - Atiek Rahmawaty; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Edwardsiella anguillarum , a highly virulent species within the Edwardsiella genus, causes significant mortality in milkfish farms in Taiwan. This study aimed to investigate the comparison of milkfish susceptibility, a newly identified host species in Taiwanese aquaculture, with other species Nile tilapia ( Oreochromis niloticus ) and Asian seabass ( Lates calcarifer ), to E. anguillarum , elucidating its pathogenicity across both seawater and freshwater aquaculture environments. The results showed milkfish exhibited the highest mortality rate of 85% within 48 h of infection, whereas Nile tilapia exhibited a mortality rate of 70% between the second‐ and tenth‐day post challenge, and seabass exhibited a mortality rate of 25% between the second‐ and sixth‐day post challenge. Gross lesions observed in milkfish included splenomegaly and haemorrhage, whereas Nile tilapia exhibited signs of ascites, exophthalmia and brain haemorrhage. Seabass displayed spleen granulomas and haemorrhage at the injection site. Histopathological analysis revealed common features across all three species, including multifocal necrosis, bacterial presence in the necrotic areas, serositis and oedema. Asian seabass also exhibited chronic lesions in the form of splenic granulomas. This study highlights the high susceptibility of milkfish and Nile tilapia to E. anguillarum , emphasizing the urgent need for further investigation into targeted vaccine development for these fish species. These results not only deepen our understanding of the differing levels of pathogenicity among the three species but also offer valuable insights for improving disease prevention and management strategies in aquaculture, including those applied within polyculture systems and for the maintenance of aquaculture water environments.

Single and combined effects of high-fat diet and ammonia nitrogen on oxidative stress, lipid accumulation and inflammation in liver of grass carp Ctenopharyngodon idella - Cheng Zhang; Wenhao Huang; Xiaotian Zhang; Pengju Li; Chi Wang; Limin Ye; Zhongzheng Xu; Julin Yuan; Haibo Yu (Aquaculture, 2024)

Variability and driving effect of aquatic gross primary productivity across long-distance inter-basin water diversion project - Cheng Lai; Xizhi Nong; Lihua Chen; Chi Zhang; Luiza C. Campos; Kourosh Behzadian; Ronghui Li (Journal of Cleaner Production, 2024)

Iron biogeochemical redox cycling dominantly controls cadmium availability in acidic paddy soils - Yang Yang; Tongxu Liu; Thomas Borch; Liping Fang; Shiwen Hu; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Xiaomin Li; Xiu Yuan; Fangbai Li (Geochimica et Cosmochimica Acta, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Efficient and comprehensive utilization of sugarcane bagasse components through vanillic acid pretreatment - Xichuang Cheng; Chi Feng; Zhiqiang Li; Weiwei Zhang; Li Ji; Kun Wang; Jianxin Jiang (Chemical Engineering Journal, 2024)

Characterizing and identifying of miRNAs involved in berberine modulating glucose metabolism of Megalobrama amblycephala - Mingyang Liu; Chang He; Tingting Zhu; Xiaoyan Jia; Li Zhang; Weibo Jiang; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Hengtong Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2024)

Effects of glycerol monolaurate on estradiol and follicle-stimulating hormones, offspring quality, and mRNA expression of reproductive-related genes of zebrafish (Danio rerio) females - Boyu Li; Limin Ye; Cheng Zhang; Ruofan Liu; Chi Wang; Xiaotian Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2024)

Comparative pathogenicity of Nocardia seriolae in Nile tilapia ( Oreochromis niloticus ), milkfish ( Chanos chanos ) and Asian seabass ( Lates calcarifer ) - Sandra Celenia Nazareth; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Nocardiosis, caused by Nocardia seriolae , has been a prominent disease in Southeast Asian aquaculture in the last three decades. This granulomatous disease reported in various fish species is responsible for significant economic losses. This study investigated the pathogenicity of N. seriolae in three cultured species in Taiwan: Nile tilapia (omnivore), milkfish (herbivore) and Asian seabass (carnivore). Administration of an infective dose of 1 × 10 6 CFU/ fish in tilapia, seabass and milkfish demonstrated mortalities of 100%, 90% and 75%, respectively. Additionally, clinical signs namely, granuloma and lesions displayed varying intensities between the groups and pathological scores. Polymerase chain reaction (PCR) amplification specific for N. seriolae was confirmed to be positive (432 bp) using NS1/NG1 primers. Post‐mortem lesions revealed the absence of granulomas in tilapia and milkfish and their presence in the seabass. Interestingly, the gut in tilapia showed an influx of eosinophils suggesting its role during the acute stages of infection. However, post‐challenge, surviving milkfish exhibited granulomatous formations, while surviving seabass progressed toward healing and tissue repair within sampled tissues. Overall, in conclusion, these results demonstrate the versatility in the immunological ability of individual Perciformes to contain this pathogen as a crucial factor that influences its degree of susceptibility.

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Identification of individual plants carrying viruses or a viroid in Pyrus betulifolia seedlings and virus-tested pear mother plants by group testing - Feng Jiang; Hanwei Li; Yinshuai Xie; Jinying Wang; Hai Chi; Qing Kan; Shangzhen Yu; Tianzhong Li; Yuqin Cheng (Journal of Plant Diseases and Protection, 2024)

Inhibition of Notch3/Hey1 ameliorates peribiliary hypoxia by preventing hypertrophic hepatic arteriopathy in biliary atresia progression - Xiaopan Chang; Shuiqing Chi; Xi Zhang; Xiangyang Li; Cheng Yu; Ying Zhou; Shaotao Tang (Histochemistry and Cell Biology, 2024)

Tannic Acid Impedes the Proliferation of Bladder Cancer Cells by Elevating Mitochondrial Pathways of Apoptosis - Chi-Cheng Li; Bruce Chi-Kang Tsai; Selvaraj Annseles Rajula; Chiung-Hung Hsu; Ming-Cheng Chen; Chia-Hua Kuo; Chung-Min Yeh; Dennis Jine-Yuan Hsieh; Wei-Wen Kuo; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Effects of zero-valent iron added in the flooding or drainage process on cadmium immobilization in an acid paddy soil - Hanbing Meng; Shiwen Hu; Zebin Hong; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Tongxu Liu; Fangbai Li; Kexue Liu; Yang Yang (Journal of Environmental Sciences, 2024)

Effect of sowing date on radiation and temperature use efficiencies of rice in the low-light region of China - Xiaofan Huang; Fei Deng; Chi Zhang; Qiuping Li; Yuxin He; Chenyan He; Xiaofeng Ai; Yujie Yuan; Li Wang; Hong Cheng; Tao Wang; Youfeng Tao; et al. (Field Crops Research, 2024)

Ship Shaft-Rate Electric Field Signal Denoising Method Based on VMD-MSS - Ye Wang; Dan Wang; Cheng Chi; Zhentao Yu; Jianwei Li; Lu Yu (Journal of Marine Science and Engineering, 2024)
The presence of complex electromagnetic noise in the ocean significantly impacts the accuracy of ship shaft-rate electric field signal detection, necessitating the development of an effective denoising method to enhance detection precision. Nevertheless, traditional denoising methods encounter issues like low frequency resolution, challenging threshold configuration, and mode mixing. This study introduces a method that integrates variational mode decomposition (VMD) with multi-window spectral subtraction (MSS). The intrinsic mode functions (IMFs) of noisy signals are extracted using VMD, and the noise components within different IMFs are identified. The spectral features of both signal and noise within different IMFs are leveraged to eliminate noise signals via MSS. Subsequently, the denoised components of IMFs are rearranged to derive the denoised ship shaft-rate electric field signals, achieving noise reduction across various frequency bands. Following validation using simulation signals and empirical data, the noise reduction efficacy of VMD-MSS surpasses that of alternative methods, demonstrating robust performance even at low signal-to-noise ratios. The marine electromagnetic noise is effectively suppressed in the empirical data, while preserving the characteristics of ship’s shaft-rate signals, thereby validating the method’s efficacy and demonstrating its practical engineering value.

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

Investigation of organic contaminants in the blubber of a blue whale (Balaenoptera musculus) first stranded on the coast of Taiwan - Jing-O. Cheng; Pei-Ling Wang; Li-Chin Chou; Chig-Wei Chang; Hao Ven Wang; Wei-Cheng Yang; Fung-Chi Ko (Environmental Science and Pollution Research, 2024)

Nocardiosis and other common diseases of cultured golden pompano ( Trachinotus blochii ) in Taiwan - Wei‐Xiao Yan; Yu‐Han Tseng; Wen‐Rou Huang; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2024)
Golden pompano ( Trachinotus blochii ) is a carnivorous teleost cultured in the Asia‐Pacific region. Fish culture in high densities and numbers results in disease outbreaks, causing huge economic losses. Here, we collected cultured golden pompanos from 2021 to 2022 and identified the pathogens isolated from the diseased fish. Out of a total of 64 clinical cases observed in both sea cages and fish ponds, it was found that Nocardia seriolae was the predominant pathogen (26%), followed by Lactococcus garvieae (13%). Trichodina spp. was the most prevalent parasite in sea cages and earthen ponds (21%), while Neobenedenia spp. was the primary parasitic pathogen (16%) in sea cages. Given these findings, further investigations were conducted, including antibiotic susceptibility and pathogenicity tests specific to N. seriolae in golden pompanos. Antibiotic susceptibility tests of N. seriolae revealed that all strains were susceptible to doxycycline, oxytetracycline, florfenicol and erythromycin but resistant to amoxicillin and ampicillin. Additionally, a pathogenicity assessment was carried out by administering an intraperitoneal injection of 0.1 mL containing 10 7 CFU of N. seriolae per fish. The mortality rates observed varied between 40% and 90%, with the P2 strain exhibiting the highest level of virulence, resulting in a cumulative mortality of 90%. Therefore, disease outbreaks in fish can be minimized by developing effective treatments and prevention methods.

The effect of dietary vitamin A supplementation on growth, gonadal development, molting, immunity, and ammonia nitrogen resistance in sub-adult male Chinese mitten crab, Eriocheir sinensis - Weibo Jiang; Xiaoyan Jia; Maorong Zhang; Wei Qiang; Xiaoxue Shen; Guangzhen Jiang; Xiangfei Li; Cheng Chi; Hengtong Liu; Wenbin Liu; Dingdong Zhang (Aquaculture, 2024)

Temperature acclimation improves high temperature tolerance of rainbow trout (Oncorhynchus mykiss) by improving mitochondrial quality and inhibiting apoptosis in liver - Hao Li; Haibo Yu; Xiaotian Zhang; Wenhao Huang; Cheng Zhang; Chi Wang; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Co-exposure of nanoplastics and arsenic causes neurotoxicity in zebrafish (Danio rerio) through disrupting homeostasis of microbiota–intestine–brain axis - Cheng Zhang; Yanyao Li; Haibo Yu; Tian Li; Limin Ye; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Spatial distribution of molybdenum in catchment sediments in the Sino-Mongolian border region - Wei Wang; Lanshi Nie; Dapeng Li; Chunjun Wang; Hanliang Liu; Xueqiu Wang; Xinbin Cheng; Qinghua Chi; Shojin Davaa; Jian Zhou (Journal of Geochemical Exploration, 2024)

Comparative study on tetraploid induction of the Fujian oyster Crassostrea angulata utilizing three typical methods - Yuanxin Liang; Geng Cheng; Xianchao Bai; Jianmin Zhou; Haining Zhang; Yong Chi; Gaowei Jiang; Chengxun Xu; Qi Li (Aquaculture International, 2024)

Spatial distribution of the critical mineral resource element titanium in China and its influencing factors - Wei Wang; Xueqiu Wang; Xuemin Liu; Bimin Zhang; Qinghua Chi; Dapeng Li; Jian Zhou; Hanliang Liu; Xinbin Cheng; Hui Wu; Chan Chang; Binbin Sun (Journal of Geochemical Exploration, 2024)

Identification, functional characterization and expression pattern of interferon-gamma (IFN-γ) and interferon-gamma receptor 1 (IFNGR1) in Nibea albiflora - Yongxin Liu; Kaihui Li; Mingming Wenren; Wei Cheng; Xu Zhou; Dongdong Xu; Changfeng Chi; Zhenming Lü; Huihui Liu (Fish & Shellfish Immunology, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Dietary nano-selenium improves health of liver and intestine of grass carp Ctenopharyngodon idella after overwintering - Limin Ye; Sha Liu; Xiaotian Zhang; Chi Wang; Pengju Li; Cheng Zhang; Hong Ji; Haibo Yu (Animal Feed Science and Technology, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Phenotypic evaluation of two genetically improved strains selected from the reciprocal hybrids of Crassostrea gigas and C. angulata - Gaowei Jiang; Yong Chi; Jianmin Zhou; Geng Cheng; Lijie Du; Chengxun Xu; Qi Li (Aquaculture, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Pathogenicity characterization of nocardiosis in orange‐spotted grouper ( Epinephelus coioides ) via exposure to nine distinct isolates of Nocardia seriolae and four administrative routes - Phuong Nguyen; Andre Giovanni; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Nocardia seriolae causes chronic nocardiosis in various marine and freshwater aquatic animals; however, grouper species have rarely been investigated. This study evaluated the pathogenicity of nocardiosis following N. seriolae infection in the orange‐spotted grouper Epinephelus coioides . Nine identified genetic isolates of N. seriolae were tested in vivo using the intraperitoneal method and observed daily for 35 days. The most virulent isolate was then used to evaluate transmission through different routes (intraperitoneal IP, intramuscular IM, oral OR, and immersion IS) in the same fish model and was observed daily for 42 days. The results showed mild variation in virulence among N. seriolae isolates. AOD107132‐2 K and OT103003‐N11 strains displayed the highest and lowest risk virulence, respectively, based on the accumulation and kinetics of mortality. IM and IP administrations showed an early phase response with early mortality by 5 dpc (30%–100%), while slower kinetics of nocardiosis occurred in the OR and IS routes with slow mortality at 35 dpc (4%–8%). Histopathology revealed typical granulomas, confirming the progression of nocardiosis in the diseased fish. These results provide the basis for further studies on the virulence profile of N. seriolae in Taiwan and a well‐suited route of administration in orange‐spotted groupers for further prevention development.

Aerobic degradation of parent triisobutyl phosphate and its metabolite diisobutyl phosphate in activated sludge: Degradation pathways and degrading bacteria - Chi Yao; Ying Li; Jing Li; Chenxue Jiang; Ke Jing; Suisui Zhang; Hanpei Yang; Cheng Liu; Lianfang Zhao (Journal of Hazardous Materials, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

A small extent of seawater intrusion significantly enhanced Cd uptake by rice in coastal paddy fields - Wenting Chi; Guojun Chen; Shiwen Hu; Xiaomin Li; Kuan Cheng; Qi Wang; Bingqing Xia; Yang Yang; Yibing Ma; Tongxu Liu (Journal of Hazardous Materials, 2023)

Acer truncatum leaves reduce lipid accumulation and improve liver and intestine health of grass carp (Ctenopharyngodon idella) fed with high-fat diet - Limin Ye; Xiaotian Zhang; Chi Wang; Sha Liu; Pengju Li; Cheng Zhang; Qinfeng Gao; Hong Ji; Haibo Yu (Aquaculture, 2023)

Flavonoids mitigation of typical food thermal processing contaminants: Potential mechanisms and analytical strategies - Bin Li; Jiaxin Wang; Zhen Cheng; Baoge Song; Chi Shu; Yi Chen; Wei Chen; Shufang Yang; Yiyun Yang; Jinlong Tian (Food Chemistry, 2023)

Sediment Instability Caused by Gas Production from Hydrate-bearing Sediment in Northern South China Sea by Horizontal Wellbore: Evolution and Mechanism - Qingchao Li; Difei Zhao; Junkai Yin; Xingyu Zhou; You Li; Peng Chi; Ying Han; Ubedullah Ansari; Yuanfang Cheng (Natural Resources Research, 2023)

Oral and inhalation bioaccessibility of mercury in contaminated soils and potential health risk to the kidneys and neurodevelopment of children in Taiwan - Ying-Lin Wang; Ming-Chien Mark Tsou; Li-Chi Lai; Zeng-Yei Hseu; Hsing-Cheng Hsi; Ling-Chu Chien (Environmental Geochemistry and Health, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Embryonic thermosensitivity and hatchling morphology differ among three species of crocodilians farm-raised in China - Dan Liu; Jia-Tian Chen; Jung-Chien Tsai; Cheng-Wang Li; Chi-Xian Lin; Yan-Fu Qu; Yu Du; Xiang Ji (Aquaculture, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Effects of disinfectants, sponge densities, water circulation rates, and vibration frequency on the artificial incubation of redclaw crayfish embryos - Cheng Shun; Jiang Wen-ping; Liu Shi-li; Chi Mei-li; Zheng Jian-bo; Liu Yi-nuo; Hang Xiao-ying; Peng Miao; Li Fei; Wang Dan-li (Aquaculture, 2023)

Spatial distribution of iodine in the pedosphere of China and its influencing factors - Wei Wang; Xueqiu Wang; Bimin Zhang; Qinghua Chi; Qingqing Liu; Jian Zhou; Xinbin Cheng; Lanshi Nie; Hanliang Liu; Dongsheng Liu; Taotao Yan; Longxue Li (Journal of Geochemical Exploration, 2023)

Cyanidin-3- O -glucoside and its phenolic metabolites ameliorate intestinal diseases via modulating intestinal mucosal immune system: potential mechanisms and therapeutic strategies - Zhen Cheng; Xu Si; Hui Tan; Zhihuan Zang; Jinlong Tian; Chi Shu; Xiyun Sun; Zhiying Li; Qiao Jiang; Xianjun Meng; Yi Chen; Bin Li; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Triisobutyl phosphate biodegradation by enriched activated sludge consortia: Degradation mechanism and bioaugmentation potential - Chi Yao; Ying Li; Chenxue Jiang; Jing Li; Ke Jing; Suisui Zhang; Hanpei Yang; Cheng Liu; Lianfang Zhao (Environmental Pollution, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Nocardia seriolae cell wall lipids: An effective protective mechanism in resistance and virulence - Sandra Celenia Nazareth; Shreesha Rao; Li‐Wu Cheng; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2023)
Piscine nocardiosis, caused by Nocardia seriolae , is a refractory granulomatous disease in South‐East Asian aquaculture. This study investigates the virulence of nocardial lipids essential for pathogenesis among Actinomycetes. Petroleum ether (PE) was used to selectively delipidate two groups of N. seriolae , namely, live cell (LC) and killed cell (KC); resulting in delipidated live cell (DLC) and delipidated killed cell (DKC), respectively. Changes post‐delipidation on genus characteristics, such as loss in acid‐fast nature and resistance to lysozyme were observed. Transmission electron microscopy revealed notable changes in the lipid layer. Additionally, Lates calcarifer , Asian seabass intraperitoneally injected with LC and DLC had mortality rates of 90% and 50%, respectively, with the latter exhibiting a delay in mortality. Reverse‐transcription quantitative PCR (RT‐qPCR) analysis of host cytokines from the spleen and head kidney showed delipidation contributed to the induction of an immune response with increased transcriptional levels of interferon‐γ ( ifn‐γ ). Histopathological samples collected on day 7 post‐inoculation displayed a varied granulomatous response between the treatment groups and scored for pathological changes. These findings affirm that the virulence of the lipids remains independent of the living state of the cell, significantly altering the immune and granulomatous responses in L. calcarifer to N. seriolae.

Nanoplastics promote arsenic-induced ROS accumulation, mitochondrial damage and disturbances in neurotransmitter metabolism of zebrafish (Danio rerio) - Cheng Zhang; Yanyao Li; Haibo Yu; Limin Ye; Tian Li; Xiaotian Zhang; Chi Wang; Pengju Li; Hong Ji; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Kojicone C, new anti-inflammatory polyketide from insect-associated fungus Aspergillus versicolor - Tian-Xiao Li; Chi Zhang; Feng-Cheng Shi; Ye Ye; Jia-Le Huang; Lei Wu; Chun-Ping Xu (Phytochemistry Letters, 2023)

Generating Sentinel-2 all-band 10-m data by sharpening 20/60-m bands: A hierarchical fusion network - Jingan Wu; Liupeng Lin; Chi Zhang; Tongwen Li; Xiao Cheng; Fang Nan (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Associations between air pollutants and hospital admissions for chronic obstructive pulmonary disease in Jinan: potential benefits from air quality improvements - Chuanlong Cheng; Chuang Han; Qidi Fang; Ying Liu; Xiangyu Chi; Xiujun Li (Environmental Science and Pollution Research, 2023)

Variational Bayesian Inference Time Delay Estimation for Passive Sonars - Feilong Ding; Cheng Chi; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2023)
In passive sonars, distance and depth estimation of underwater targets is often limited by the accuracy of time delay estimations. The estimation accuracy of the existing methods of time delay estimation is limited by the uniform discrete grid (signal sampling rate). When a true time delay is out of the grid, the estimation accuracy deteriorates due to the mismatch between the real-time delay and the discrete grid. This paper proposes a new method for time delay estimation, which realizes the time delay estimation under the framework of variational Bayesian inference. The proposed method is grid-less, that is, continuous in the time domain. Unlike the popular grid-less compressive time delay estimation method, this method does not require parameter adjustment, and can automatically estimate the number of time delays, noise variance, and amplitude variance. The simulation results showed that the performance of the proposed method was superior to the reference state-of-the-art time delay estimation methods.

Effects of light color, photoperiod, and growth-related gene interference or overexpression on the survival, growth, or physiological and biochemical indices of red claw crayfish juveniles - Shun Cheng; Jian-bo Zheng; Yong-yi Jia; Mei-li Chi; Wen-ping Jiang; Shi-li Liu; Fei Li; Yi-nuo Liu; Zhi-min Gu; Dan-li Wang (Aquaculture, 2023)

Changes in the gene expression and gut microbiome to the infection of decapod iridescent virus 1 in Cherax quadricarinatus - Jianbo Zheng; Yongyi Jia; Fei Li; Meili Chi; Shun Cheng; Shili Liu; Wenping Jiang; Yinuo Liu (Fish & Shellfish Immunology, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

From lab to practical: An ammonia-powered fuel cell electric golf cart system - Lingling Zhai; Chiu Shek Wong; Honglei Zhang; Pei Xiong; Xiangdang Xue; Yiu Lun Ho; Cuidong Xu; Yat Chi Fong; Jie Mei; Wing Wa Chan; Shu Chuen Ip; Shuangxia Niu; et al. (Chemical Engineering Journal, 2023)

Waveform Design Using Coprime Frequency-Modulated Pulse Trains for Reverberation Suppression of Active Sonar - Xiaobin Cui; Cheng Chi; Shuqiu Li; Zigao Li; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
Over the last two decades, low-frequency active sonar has become an attractive tool for underwater target detection. The reverberation to signal ratio (RSR) of transmitted waveforms is an important factor affecting the detection capability of low-frequency active sonar. Therefore, reasonable waveform design for reverberation suppression of active sonar is an important topic. Pulse trains of linear frequency-modulated (PTFM) waveforms have been proposed and manifested their good performance in suppressing reverberation. The number of sub-pulses is positively related to the reverberation to signal ratio; the lower the number of sub-pulses, the lower the reverberation to signal ratio. However, to avoid ambiguity in a Doppler measurement, the PTFM waveforms have a requirement for the number of sub-pulses to be satisfied, which prevents its reverberation suppression performance from being further improved. In this paper, we propose a coprime pulse train of linear frequency-modulated (CPTFM) waveform, which reduces the number of sub-pulses to some extent. Therefore, the ability of reverberation suppression of the CPTFM waveform can be improved. The RSR was chosen as the metric to evaluate the waveform’s ability to suppress reverberation, and the theoretical formula for the RSR of the CPTFM waveform was derived in zone A and B. With the overlap of zones A and B brought about by the decrease in the number of sub-pulses, the average RSR of zones A and B is used in this paper to evaluate the reverberation suppression ability of the waveform. The simulation experiment shows that the proposed CPTFM waveform decreases the average RSR by 7 dB and 20 dB in comparison to the reference PTFM waveform and continuous waveform (CW), which is consistent with the theoretical results by the derived formulas.

Structural deformation, metallogenic epoch and genetic mechanism of the Woxi Au-Sb-W deposit, Western Hunan Province, South China - Bin Li; Deru Xu; Daoyuan Bai; Guoxiang Chi; Junfeng Dai; Cheng Gao; Teng Deng; Shaohao Zou; Wen Ma; Guojian Wang; Yuexin Ling; Guangqian Zeng; et al. (Science China Earth Sciences, 2022)

Tannic acid attenuate AKT phosphorylation to inhibit UMUC3 bladder cancer cell proliferation - Ming-Cheng Chen; Selvaraj Annseles Rajula; V. Bharath Kumar; Chiung-Hung Hsu; Cecilia Hsuan Day; Ray-Jade Chen; Tso-Fu Wang; Vijaya Padma Viswanadha; Chi-Cheng Li; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2022)

Selenium improved mitochondrial quality and energy supply in the liver of high-fat diet-fed grass carp (Ctenopharyngodon idella) after heat stress - Xiaotian Zhang; Haibo Yu; Xianfang Yan; Pengju Li; Chi Wang; Cheng Zhang; Hong Ji; Qinfeng Gao; Shuanglin Dong (Fish Physiology and Biochemistry, 2022)

Dietary sea buckthorn polysaccharide reduced lipid accumulation, alleviated inflammation and oxidative stress, and normalized imbalance of intestinal microbiota that was induced by high-fat diet in zebrafish Danio rerio - Ying Lan; Chi Wang; Cheng Zhang; Pengju Li; Jinding Zhang; Hong Ji; Haibo Yu (Fish Physiology and Biochemistry, 2022)

Toxic Effect of Combined Exposure of Microplastics and Copper on Goldfish (Carassius auratus): Insight from Oxidative Stress, Inflammation, Apoptosis and Autophagy in Hepatopancreas and Intestine - Cheng Zhang; Limin Ye; Chi Wang; Xiaofan Xiong; Yanyao Li; Pengju Li; Xiaotian Zhang; Haibo Yu (Bulletin of Environmental Contamination and Toxicology, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Underwater Tone Detection with Robust Coherently-Averaged Power Processor - Qichen Xie; Cheng Chi; Shenglong Jin; Guanqun Wang; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2022)
The detection of tonal signals with unknown frequencies is an important area of study in underwater signal processing. A common approach to address this issue is to use the Discrete Fourier Transform (DFT) for observations. When a tone does not lie precisely at the discrete DFT frequency point, its energy will leak to adjacent frequency point. This phenomenon is known as scalloping loss or Picket Fence Effect (PFE). PFE leads to the degradation of detection performance based on DFT. This paper studies the problem of robust detection in the case of PFE. A coherently-averaged power processor utilizing the information of adjacent frequency bins is designed. The results of simulations and experiments show that the proposed method is robust against PFE, and is highly suitable for tone detection in practical circumstances.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Experimental Investigation of Decoupled Charge Effect on Rock Fragmentation by Blasting - Li Yuan Chi; Cheng Wang; Zong-Xian Zhang; Xuan Xu; Jun Yang (Rock Mechanics and Rock Engineering, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Analysis of the Winter Cloud-to-Ground Lightning Activity and Its Synoptic Background in China during 2010–20 - Manman Ma; Xiaogang Huang; Jianfang Fei; Chi Zhang; Chao Li; Xiaoping Cheng (Advances in Atmospheric Sciences, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

First report of acanthocephalan parasite, Longicollum pagrosomi Yamaguti, 1935 in cultured red snapper ( Lutjanus erythropterus ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2022)
For the first time, Longicollum pagrosomi Yamaguti, 1935, an acanthocephalan parasite, has been characterized with morphological, histopathological and molecular detail in farmed red snapper ( Lutjanus erythropterus ) in Taiwan. The diseased fish showed clinical signs of anorexia, emaciation and were gasping for air at the water's surface. Gross examination revealed extensive necrosis in the intestine and even penetration at the site of parasitic attachment, resulting in a large number of parasites being lodged in the peritoneal cavity, surrounded by black hyperplastic connective tissue. The parasites collected from the intestine were studied using optical microscopy, histopathology, scanning electron microscopy (SEM) and molecular phylogenetic analysis. They were creamy white in colour, and were separated into their proboscis, neck and metasoma (trunk) under optical microscopy. Histopathological examination revealed ovarian balls (floating ovaries) inside the ligament sac and eggs within the egg sorting apparatus. The SEM images revealed that the proboscis had 11–14 longitudinal rows with 9–12 recurrent, backward‐facing, organized hooks. In the 18S and 28S phylogenetic tree, sequences of the specimens were identical to those of other Longicollum pagrosomi , in addition to the morphological features. Thus, we confirmed that the parasites belonged to Longicollum pagrosomi in this study.

Adaptation capability of rainfall hotspots in water resilient cities using QGIS: a case study of Taichung City in Taiwan - Ming-jen Cheng; Wei-liang Sia; Feng-chi Liao; Li-shin Chang (Environmental Monitoring and Assessment, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Demographics of Scomberomorus commerson in the Central Taiwan Strait - Jinn-Shing Weng; Li-Chi Cheng; Yun-Sin Lo; Jen-Chieh Shiao; Jia-Sin He; Ming-An Lee; Kwang-Ming Liu (Journal of Marine Science and Engineering, 2021)
The narrow-barred Spanish mackerel Scomberomorus commerson is an economically essential species; however, few studies have investigated its demographic structure in the northwestern Pacific, which includes Taiwan’s waters. This study examined the growth parameters, age composition, mortality, and sex ratio of S. commerson catches by examining sagittal otoliths and other biological data collected in a 3-year project from June 2018 to June 2021. The transverse sections of sagittal otoliths exhibited alternating translucent and opaque zones, in annual cycles, and this observation was validated by otolith edge analysis. Opaque zones began to form in October; the growth peaked in December and lasted until March. Growth parameters were estimated for female (L∞ = 144.1 cm fork length [FL], k = 0.39 y−1, to = −0.85 y) and male (L∞ = 136.0 cm FL, k = 0.32 y−1, to = −1.49 y) specimens. The maximum recorded FL, body weight, and age were 159.0 cm, 27 kg, and 9.2 y for female and 135.0 cm, 17.8 kg, and 7.2 y for male specimens. Rapid growth was observed for both sexes, with FL reaching 66.8 ± 14.2 cm in female specimens and 70.1 ± 11.0 cm in male specimens during the first year of life. An age–length key based on the direct otolith aging and FL dataset (N = 646) was used to estimate the age composition of 3-year catches measured at landing (N = 16,133). The results verified that the S. commerson currently caught in the central Taiwan Strait are mainly young fish aged 1+ to 2+ y. The estimated fishing mortality (0.27 y−1) and exploitation rate (0.30) suggested that overfishing was not occurring in this stock. The findings of this study have helped clarify the population dynamics of the S. commerson in the Taiwan Strait, and the biological parameters reported herein can aid the management and conservation to ensure the sustainability of this species in this region.

Genotype and virulence gene analyses of Bacillus cereus group clinical isolates from the Chinese softshell turtle ( Pelodiscus sinensis ) in Taiwan - Li‐Wu Cheng; Shreesha Rao; Sayuj Poudyal; Pei‐Chi Wang; Shih‐Chu Chen (Journal of Fish Diseases, 2021)
Chinese softshell turtles ( Pelodiscus sinensis ) (CST) are susceptible to infections by bacteria belonging to the Bacillus cereus group (Bcg). Bcg includes several closely related species, two of which, B . cereus and B . thuringiensis , are pathogens of aquatic animals or insects. In the present study, we collected 57 Bcg isolates from diseased CST from 2016 to 2019 in Kaohsiung and Pingtung, where most CST farms are located in Taiwan. All isolates were divided into four genotypes with two restriction enzymes, Sma I and Not I, by pulsed‐field gel electrophoresis and enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC‐PCR). Representative isolates from each genotype were subjected to phylogenetic tree analysis using 16S rDNA and pyruvate carboxylase genes as phylogenetic markers, and these CST isolates appeared in different clades. PCR was performed targeting six selected virulence genes, four of which were detected in CST isolates, including cytotoxin K (1/57), hblC of the haemolysin BL complex (46/57), nheA of the non‐haemolytic enterotoxin complex (52/57) and enterotoxin FM (57/57), whereas cereulide synthetase and cereulide peptide synthase‐like genes were not detected in any isolates.

Dietary berberine can ameliorate glucose metabolism disorder of Megalobrama amblycephala exposed to a high-carbohydrate diet - Chang He; Xiaoyan Jia; Li Zhang; Fan Gao; Weibo Jiang; Chuang Wen; Cheng Chi; Xiangfei Li; Guangzhen Jiang; Haifeng Mi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Degradation stage effects on vegetation and soil properties interactions in alpine steppe - Cheng-yang Li; Fei Peng; Xian Xue; Chi-min Lai; Wen-juan Zhang; Quan-gang You; Xiao-jie Chen; Xue-qin Zhang; Tao Wang (Journal of Mountain Science, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

Mechanical injury and IL-1β regulated LOXs and MMP-1, 2, 3 expression in ACL fibroblasts co-cultured with synoviocytes - Chunli Wang; Qingjia Chi; Yongqiang Sha; Kang Xu; Chunming Xu; Cheng Chen; Wei Huang; Peixing Chen; Peter Chen; Li Yang; K. L. Paul Sung (Biotechnology Letters, 2020)

DhLHY, a Circadian Expressed Gene of Doritaenopsis Hybrid, Promotes Floral Transition in Low Temperature, but Postpones Flowering in Overexpressed Transgenic Arabidopsis - Chi Zhang; Qian Cheng; Haiyan Li; Ping Luo; Yongyi Cui (Tropical Plant Biology, 2020)

The association between prenatal endocrine-disrupting chemical exposure and altered resting-state brain fMRI in teenagers - Jun-Cheng Weng; Chi Ieong Hong; Jeng-Dau Tasi; Chao-Yu Shen; Pen-Hua Su; Shu-Li Wang (Brain Structure and Function, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Methamphetamine-Induced Cognitive Deficits and Psychiatric Symptoms Are Associated with Serum Markers of Liver Damage - Tingting Zhao; Changping Zhai; Hongmei Song; Yanhai Wu; Chuanhui Ge; Yonglin Zhang; Hongxia Xu; Zhengsuo Chi; Hui Chu; Wei Shi; Xiaodong Cheng; Xin Li; et al. (Neurotoxicity Research, 2020)

Selection of reference genes for miRNA quantitative PCR and its application in miR-34a/Sirtuin-1 mediated energy metabolism in Megalobrama amblycephala - Jie Liu; Erteng Jia; Huajuan Shi; Xiangfei Li; Guangzhen Jiang; Cheng Chi; Wenbin Liu; Dingdong Zhang (Fish Physiology and Biochemistry, 2019)

Molecular characterization and expression analysis of cyp19a gene in Culter alburnus - Jianbo Zheng; Yongyi Jia; Fei Li; Shili Liu; Meili Chi; Shun Cheng; Zhimi Gu (Fisheries Science, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Preparation of AgCl/TNTs nanocomposites for organic dyes and inorganic heavy metal removal - Cheng-Yen Tsai; Chen-Wuing Liu; Hsing-Cheng Hsi; Kuen-Song Lin; Yi-Wen Lin; Li-Chi Lai; Tsung-Nan Weng (Environmental Science and Pollution Research, 2019)

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Assessment of heavy metal in coal gangue: distribution, leaching characteristic and potential ecological risk - Chunyu Hua; Guangzhu Zhou; Xin Yin; Cuizhen Wang; Baorong Chi; Yiyun Cao; Yue Wang; Yin Zheng; Zirui Cheng; Ruyue Li (Environmental Science and Pollution Research, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Comparison of stomach microRNA transcriptomes of Tibetan and Yorkshire pigs by deep sequencing - Wen-kui Sun; Yanyue Li; Chi Cheng; Yi-hui Chen; Kai Zeng; Xiaohui Chen; Yiren Gu; Rui Liu; Xuebin Lv; Rong Gao (Genes & Genomics, 2018)

Permineralized Calamitean Axes from the Upper Permian of Xinjiang, Northwest China and Its Paleoecological Implication - Fayao Chen; Xiao Shi; Jianxin Yu; Hongfei Chi; Jun Zhu; Hui Li; Cheng Huang (Journal of Earth Science, 2018)

Role of the meridional dipole of SSTA and associated cross-equatorial flow in the tropical eastern Pacific in terminating the 2014 El Niño development - Yi-Kai Wu; Lin Chen; Chi-Cherng Hong; Tim Li; Cheng-Ta Chen; Lu Wang (Climate Dynamics, 2018)

Acidity of Aerosols during Winter Heavy Haze Events in Beijing and Gucheng, China - Xiyuan Chi; Pengzhen He; Zhuang Jiang; Xiawei Yu; Fange Yue; Longquan Wang; Bokun Li; Hui Kang; Cheng Liu; Zhouqing Xie (Journal of Meteorological Research, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Inhibition of P2X7 Receptor Ameliorates Nuclear Factor-Kappa B Mediated Neuroinflammation Induced by Status Epilepticus in Rat Hippocampus - Cheng Huang; Xiao-sa Chi; Rui Li; Xin Hu; Hai-xia Xu; Jin-mei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

The function of OsbHLH068 is partially redundant with its homolog, AtbHLH112, in the regulation of the salt stress response but has opposite functions to control flowering in Arabidopsis - Hung-Chi Chen; Vicki Hsieh-Feng; Pei-Chun Liao; Wan-Hsing Cheng; Li-Yu Liu; Yun-Wei Yang; Ming-Hsin Lai; Men-Chi Chang (Plant Molecular Biology, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Inhibition of mTOR Pathway by Rapamycin Decreases P-glycoprotein Expression and Spontaneous Seizures in Pharmacoresistant Epilepsy - Xiaosa Chi; Cheng Huang; Rui Li; Wei Wang; Mengqian Wu; Jinmei Li; Dong Zhou (Journal of Molecular Neuroscience, 2017)

Nitrogen removal in wood chip combined substrate baffled subsurface-flow constructed wetlands: impact of matrix arrangement and intermittent aeration - Huai Li; Zifang Chi; Baixing Yan; Long Cheng; Jianzheng Li (Environmental Science and Pollution Research, 2017)

Microsporomyces hainanensis sp. nov., Isolated from Hybrid Rice (Oryza sativa L.) Seeds - Feirong Bai; Yang Liu; Ni Li; Su Yao; Nannan Li; Weiping Wang; Chi Cheng (Current Microbiology, 2016)

Pioglitazone inhibits advanced glycation end product-induced matrix metalloproteinases and apoptosis by suppressing the activation of MAPK and NF-κB - Hai-Bin Zhang; Ying Zhang; Cheng Chen; Yu-Qing Li; Chi Ma; Zhao-Jun Wang (Apoptosis, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Composition, distribution and habitat effects of vascular plants on the vertical surfaces of an ancient city wall - Yanning Qiu; Bin J. W. Chen; Yanjuan Song; Zheng Y. X. Huang; Li Wan; Cheng Huang; Maosong Liu; Chi Xu (Urban Ecosystems, 2016)

Short-Term Effects and Safety Analysis of Retrograde Autologous Blood Priming for Cardiopulmonary Bypass in Patients with Cardiac Valve Replacement Surgery - Ming Cheng; Jun-Quan Li; Tian-Chi Wu; Wei-Chen Tian (Cell Biochemistry and Biophysics, 2015)

Combined effects of the BDNF rs6265 (Val66Met) polymorphism and environment risk factors on psoriasis vulgaris - Cheng Quan; Kun-Ju Zhu; Chi Zhang; Zhong Liu; Huan Liu; Cheng-Yao Zhu; Ke-Shen Li; Yi-Ming Fan; Jie Zheng (Molecular Biology Reports, 2014)

Mutations in Ralstonia solanacearum loci involved in lipopolysaccharide biogenesis, phospholipid trafficking and peptidoglycan recycling render bacteriophage infection - Yu-Hau Hong; Chi Huang; Kuan-Chung Wang; Tai-Hsiang Chu; Chien-Hui Li; Yu-Ju Chu; Chiu-Ping Cheng (Archives of Microbiology, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Measurements and modeling of open-channel flows with finite semi-rigid vegetation patches - Cheng Zeng; Chi-Wai Li (Environmental Fluid Mechanics, 2014)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Environmental assessment of polycyclic aromatic hydrocarbons in the surface sediments of a remote region on the eastern coast, Taiwan - Jun-Yi Kuo; Fung-Chi Ko; Jing-O Cheng; Pei-Jie Meng; Jan-Jung Li; Chin-Chang Hung (Environmental Monitoring and Assessment, 2012)

Eicosadienoic acid differentially modulates production of pro-inflammatory modulators in murine macrophages - Yung-Sheng Huang; Wen-Cheng Huang; Chi-Wei Li; Lu-Te Chuang (Molecular and Cellular Biochemistry, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

Emerging threat of thrips-borne Melon yellow spot virus on melon and watermelon in Taiwan - Jui-Chu Peng; Shyi-Dong Yeh; Li-Hsin Huang; Ju-Ting Li; Yuan-Fu Cheng; Tsung-Chi Chen (European Journal of Plant Pathology, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

China’s wetland change (1990–2000) determined by remote sensing - Peng Gong; ZhenGuo Niu; Xiao Cheng; KuiYi Zhao; DeMin Zhou; JianHong Guo; Lu Liang; XiaoFeng Wang; DanDan Li; HuaBing Huang; Yi Wang; Kun Wang; et al. (Science China Earth Sciences, 2010)

Serological relationship between Melon yellow spot virus and Watermelon silver mottle virus and differential detection of the two viruses in cucurbits - Tsung-Chi Chen; Yun-Yueh Lu; Ying-Huey Cheng; Ju-Ting Li; Yi-Chun Yeh; Ya-Chi Kang; Chia-Peng Chang; Li-Hsin Huang; Jui-Chu Peng; Shyi-Dong Yeh (Archives of Virology, 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

Chemical constituents from the leaves of Machilus zuihoensis Hayata var. mushaensis (Lu) Y.C. Liu - Chung-Yi Chen; Ming-Jen Cheng; Yi-Jung Chiang; Jia-Chi Bai; Chih-Tsao Chiu; Rong-Jyh Lin; Yen-Ray Hsui; Wen-Li Lo (Natural Product Research, 2009)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)